“Edige” is the undying spiritual heritage of the Karakalpak people - Aytmuratov J. (Золотоордынское обозрение)
The aim of the research is to study the role of researchers in the process of studying and widely popularizing the dastan of “Edige” among the Karakalpak people, as well as to analyze its significance as an important element of spiritual heritage. Researchmaterials: The basis of the researchis a variety of Karakalpakvariants of the dastan of “Edige”,aswell as scientificworks by bothRussianandKarakalpakresearchersdevoted to thiswork.Specialattention is paid to the variant of the dastanrecordedfrom the wordsof Erpolat zhyrau, one whichstands out for itsdepthandbrightness in the ideologicalimages of the heroes. The scientific novelty of this research lies in a comprehensive analysis of the relationship between the images of the heroes of the Karakalpak dastan of “Edige” with historical events, something which allows us to identify the deep cultural and historical roots of this work. Unlike existing studies, the emphasis in this work is on the predominant influence of the worldview of the Karakalpak people on the image of heroes, expressed through the prism of zhyrau’s creativity. In addition, the research focuses on a unique version of the dastan of “Edige”, presented in the Karakalpak tradition, which reflects the memories of the population of the Southern Aral Sea region and their longing for the banks of the Volga and Yaik rivers. Results of the research: this study confirms the importance of the dastan of “Edige” as a piece of the inextinguishable cultural heritage of the Karakalpak people. During the analysis, the following key conclusions were reached: The images of the heroes of the dastan of “Edige” are closely related to historical events, which allows a deeper understanding of the cultural and social contexts in which this folklore epic was formed. The research showed that the worldview of the Karakalpak people significantly affects the image of heroes, expressed in their moral and ethical qualities, as well as in their actions which reflected the values and ideals of their society.